Neutrophil-Lymphocyte Ratio in Small Renal Masses. (12th March 2014) - Bazzi, Wassim M.; Dejbakhsh, Sheila Z.; Bernstein, Melanie; Russo, Paul
Abstract : Introduction . To evaluate the association between preoperative neutrophil-lymphocyte ratio (NLR) and clinicopathologic characteristics in patients with small renal masses (SRM). Methods . Retrospective chart reviews of patients with renal masses ≤4 cm who underwent nephrectomy from January 2007 to July 2012 were conducted. Multivariable linear regression was used to examine the association between preoperative NLR and clinicopathologic variables. Results . In 1001 patients, we noted higher mean preoperative NLR in men (3.0 ± 1.4 versus2.6 ± 1.3 in women, P < 0.01 ) and Caucasians (2.9 ± 1.4 versus1.9 ± 0.9 in African Americans, P < 0.01 ) but no significant differences in patients with low (I-II) versus high (III-IV) American Society of Anesthesiologists (ASA) scores (2 . 8 ± 1.4 versus2 . 9 ± 1.5, P = 0 . 18 ) or benign versus malignant pathology (2.9 ± 1.4 versus2.8 ± 1.3, P = 0 . 75 ). Spearman correlation analysis (ρ ) showed preoperative NLR significantly correlated with age (ρ = 0.15, P < 0.01 ) and preoperative serum creatinine (Crea) [ρ = 0.13, P < 0.01 ]. On multivariable linear regression analysis older age, male gender, Caucasian race, and preoperative Crea were predictive of higher preoperative NLR, but ASA score and tumor pathology were not. Conclusions . In patients with SRM, we found no association between preoperative NLR and tumor pathology.